2008
DOI: 10.1364/oe.16.007564
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast gaseous “half-wave plate”

Abstract: Abstract:We demonstrate that filaments generated by ultrashort laser pulses can induce a remarkably large birefringence in Argon over its whole length, resulting in an ultrafast "half-wave plate" for a copropagating probe beam. This birefringence originates from the difference between the nonlinear refractive indices induced by the filament on the axes parallel and orthogonal to its polarization. An angle of 45° between the filament and the probe polarizations allows the realization of ultrafast Kerr-gates, wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 28 publications
1
37
0
Order By: Relevance
“…Accordingly, THz pulse could be generated along both orthogonal axes. Two components would travel at different phase velocities due to the substantial difference in the non-linear refractive indices generated by the femtosecond laser pulse along its polarization axis and the orthogonal axis, respectively [11]. Finally, an elliptically polarized THz pulse could be generated at the output of the filament.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, THz pulse could be generated along both orthogonal axes. Two components would travel at different phase velocities due to the substantial difference in the non-linear refractive indices generated by the femtosecond laser pulse along its polarization axis and the orthogonal axis, respectively [11]. Finally, an elliptically polarized THz pulse could be generated at the output of the filament.…”
Section: Resultsmentioning
confidence: 99%
“…In details, two orthogonally polarized THz wave could be generated by either four-wave rectification [8] or second order rectification due to the spatial asymmetry of filament plasma. Taking into account the optical birefringence brought forth by femtosecond laser pulse [11], the output THz pulse from the filament could be elliptically polarized depending on the amplitude and phase difference of two orthogonal polarization components.…”
Section: Introductionmentioning
confidence: 99%
“…1(b)] and the orthogonal y axis. Integrated over the whole interaction length, the birefringence induces a dephasing between the probe beam's components along the fast and slow polarization axes [23]:…”
Section: Theoretical Analysesmentioning
confidence: 99%
“…The linearly polarized probe pulse becomes elliptically polarized; its major axis rotates in the course of propagation [22]. Recently, it was proved by Béjot et al [23] that filament-induced symmetry breaking in argon gas can act as a "gaseous half-wave plate" for the probe. Later Marceau et al [24], Chen et al [25], and Calegari et al [26] demonstrated that filament in molecular gases can spatially separate the orthogonal polarizations of a probe pulse with the parallel-to-pump polarization component guided along the propagation axis, and the perpendicular-to-pump polarization component defocused outside.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the FROG measurements require to distill polarization gating of different origins. Although Kerr effect induced ultrafast transient birefringence could also be used to realize a PG-FROG, it is critically dependent on the strong excitation pulses [10,11]. Such an instantaneous gating is originated from Kerr induced changes of nonlinear refractive index within the pump pulse duration that differentiate parallel and orthogonal to the pump field polarization, while molecular optical gating exhibits a delayed response due to the rotational Raman excitation of molecules.…”
mentioning
confidence: 99%